Czy możliwa jest mutacja „banoptykonu” w „careoptykon”? O szansach na przeciwdziałanie prekaryzacji i wykluczeniu migrantów oraz uchodźców - Rzońca, Apolinary (Zagadnienia Rodzajów Literackich, 2022)
The main focus of this article is an attempt to answer the title research question: is it possible to mutate a banopticon into a careopticon? The article offers an interdisciplinary look at selected narratives, from three categories: film, television theatre and prose. All three works deal in their own way with migration, which takes on different faces. The article distinguishes the main characters into migrants and refugees, while pointing out their common features. The struggles of the newcomers with the difficult reality in a foreign land are described. The author deliberately translated and quoted fragments of a novella by Abdulrazak Gurnah, hitherto unknown and not translated into Polish, who received the Nobel Prize in Literature in 2021 for showing the effects of colonialism and for depicting the fate of refugees with human compassion. The analysis of works selected for the purpose of the article is to serve, in particular, critical reflection on contemporary problems that are discussed on the pages of literature in the humanities, social sciences, and economics. In the article the notion of “exclusion” is extensively illustrated, which is contrasted with some proposals of systemic solutions related to the notion of “care”. The author is of the opinion that contemporary humanities, especially literary studies, should enter interdisciplinary fields, where at the intersection a field for critical reflection on reality is created in order to define the problems of civilisation and attempt to solve them effectively.